Presence of vascular adventitial fibroblastic cells in diffuse-type gastric carcinomas. Issue 9 (27th August 2004) - Nakayama, H; Enzan, H; Miyazaki, E; Kuroda, N; Toi, M; Hiroi, M; Yasui, W
Abstract : Aim: To investigate morphological changes in the tumour vessel adventitia, particularly the distribution of vascular adventitial fibroblastic cells (VAFCs)—namely, CD34 positive fibroblastic cells just outside the vascular media—in diffuse-type gastric carcinomas. Method: In total, 18 surgically resected advanced typical diffuse-type gastric carcinomas and their normal tissues were examined. Immunostaining for CD34, CD31, high molecular weight caldesmon (HCD), and cytokeratin 8 (CAM5.2) was performed to detect VAFCs. VAFCs are positive for CD34 but negative for CD31, and are located just outside the vascular media (HCD positive vascular smooth muscle bundle). The areas just outside the vascular media in the whole maximum tumour cut surface were assessed, except the tumour growing edge, which was confirmed by immunostaining with CAM5.2. CD34 positive and CD31 negative cells just outside the vascular media were defined as VAFCs. Results: VAFC containing vessels were seen in 17 of the 18 diffuse carcinoma tissues. Vessels lacking VAFCs were also detected in these 17 tumours. In contrast, all of the vessels lacked VAFCs in the remaining tumour. In the 18 samples of normal tissue, all of the vessels contained VAFCs. Conclusions: These results suggest that the presence of VAFCs is associated with the infiltration of diffuse scattered gastric carcinoma cells.